Acoustic properties for Ga–Sn–Zn liquid metal coupler with low melting point and high acoustic impedance. (1st July 2023) - Ohashi, Yuji; Murakami, Rikito; Yamaguchi, Hiroaki; Yokota, Yuui; Yoshikawa, Akira
Abstract: Acoustic properties of Ga–Sn–Zn (GSZ) liquid alloy coupler with high acoustic impedance were investigated to evaluate materials with high acoustic impedance. GSZ liquid alloy was prepared and its longitudinal wave velocity and attenuation coefficient were measured using the plane-wave ultrasonic material characterization system. Density of the GSZ liquid alloy was also measured by a constant volume expansion method. The acoustic impedance of the GSZ was 12 times higher than that of the water. Attenuation coefficient of GSZ is much smaller than that of water, exhibiting 7.6 dB mm −1 for water and 0.5 dB mm −1 for GSZ at 200 MHz. Considering the reflection and transmission coefficients at each medium boundary calculated from the experimentally obtained acoustic impedance, it was suggested that the amplitude of the reflected wave from the back surface of the Ir sample can be made about 30 times larger with the GSZ coupler than with the water coupler.